607. Group B Streptococcus Resistance to Clindamycin: Regional Antibiogram Surveillance in Los Angeles County. (26th November 2018) - Krug, Cary; Terashita, Dawn; Knight, Wendy Manuel; Bhaurla, Sandeep; Felix-Mendez, Joanna; Miner, Aaron; Bloomfield, Leah; Ha, David; Butler-Wu, Susan; Fernandes, Priyanka; Garner, Omai; McKinnell, James
Abstract: Background: Intrapartum antibiotic prophylaxis (IAP) prevents neonatal mortality from Group B Streptococcus (GBS). Clindamycin resistance among GBS isolates complicates IAP for GBS-positive women allergic to penicillin and cephalosporins. GBS screening by nucleic acid amplification tests (NAATs) provides rapid results, but no susceptibility data to inform IAP. We sought to estimate burden of clindamycin resistance among GBS in Los Angeles County (LAC). Methods: Hospital antibiogram data were gathered from all LAC acute care hospitals from 2015 to 2016. Weighted averages for GBS resistance to clindamycin, erythromycin, penicillin, and TMP/SMX were calculated. Facilities which reported clindamycin susceptibilities were interviewed regarding antimicrobial susceptibility testing methods. Results: A total of 2, 339 GBS isolates from 22 hospitals were reported between 2015 and 2016. Thirteen hospitals tested GBS for clindamycin (nine reported in 2015 and 2016, four hospitals reported in 2016 only). Clindamycin resistance was found in 61.7% of 1, 794 GBS isolates (79.3% of 891 in 2015, 44.3% of 903 in 2016). Erythromycin resistance was 42% in 735 isolates reported, 0.1% penicillin of 1, 916 isolates reported, and 1.5% TMP/SMX of = 135 isolates reported. Facilities tested GBS by manual minimum inhibitory concentration (MIC) broth dilution ( n = 1), automated MIC dilution ( n = 4), agar plate diffusion ( n = 1), and MIC dilution followed by agar plate diffusion ( n = 1). Two hospitals did not perform testing on-site. Conclusion: The 62% prevalence of clindamycin-resistant GBS in LAC is three-fold higher than national CDC estimates and complicates IAP for GBS-positive women allergic to penicillin and cephalosporins. These data support CDC recommendations for susceptibility testing in addition to NAAT screening which does not include assays for common determinants of clindamycin resistance, erm -methylase, mef, and isa . There is an opportunity for diagnostic manufacturers and clinical labs to help clinicians choose appropriate IAP and prevent neonatal mortality. The CDC and public health should be aware of regional variations in clindamycin resistance. Clinicians should be aware of local resistance to inform IAP stewardship recommendations. Disclosures: S. Butler-Wu, BioFire (bioMerieux): Investigator, Research support.